Hubungan antara Status Gizi dengan Anemia pada Ibu Hamil - Faradhila, Alifani Faiz; Limbong, Marisa Marcelina; Verra Novitasari (ProHealth Journal, 2025)
One of the nutritional disorders that is still frequently encountered and a major nutritional problem in Indonesia is anemia. This condition indicates that anemia rates are quite high in Indonesia, exceeding the threshold for serious public health issues, with a prevalence limit of 40%. Although the government has implemented programs to combat anemia in pregnant women by providing 90 iron tablets to pregnant women throughout their pregnancy to reduce the incidence of anemia, the occurrence of anemia remains high. The purpose of this study is to determine the relationship between nutritional status and the incidence of anemia in pregnant women at Aisyah Health House, Bogor City, in 2024. The sample for this study consists of 50 pregnant women. This research uses a cross-sectional study design. The results show that 30 pregnant women (60%) experience anemia, and there is a statistically significant relationship between nutritional status and anemia in pregnant women (p-value 0.000). Therefore, preventive efforts in the form of focused education regarding nutritional preparation before pregnancy are necessary to reduce the incidence of anemia in pregnant women